PROSES SERTIFIKASI GURU DI SMA WIDYA KUTOARJO - MAFTUHAH, ANI (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
Background: The research goals to determine the teacher certification process in Widya senior high school Kutoarjo , the impact of certification, the barriers faced by certified teacher in Widya senior high school Kutoarjo , the efforts of  certified teacher educators to improve competence in Widya senior high school  Kutoarjo. Methode: The type of this research is descriptive qualitative research was carried out in Widya senior high school  Kutoarjo, Purworejo, Central Java. Data source is the headmaster, deputy head of curriculum affairs, DPK certified teachers, GTY  certified teachers, secretary of  Widya Educational Foundation, and the students of  XI IPS. Data was collected through observation, interview and recording documents.The results: The certification process should be observed by all teachers that really work well according to the rules. Teachers who complete the certification requirements will follow the participants, followed by the socialization of the Department of Education, charging component portfolios , portfolio assessment, to implementation and acceptance PLPG educator certificate .Impact can be categorized as economically certification can increase the income of teachers, there is an increase in competence is quite good, especially in the administration learning the learning process, trying to learn about information technology and internet media, also the burden on teachers to teach 24 hours per week must be met , as well as the performance of teachers is still low. Barriers often faced by educators certified teachers include school infrastructure is not yet complete, school finance limited budget to improve the competence of teachers, there are teachers who do not want to learn IT based, mental performance and  difficult to change the teacher, students are not familiar technology, the lack of support for the school program, the efforts to be done, among others, the school must complete the infrastructure for teaching and learning activities and to motivate teachers to improve their competence, teachers seek training, education in the field, teachers must learn information technology communications, computers and even the Internet, as well as completing all the administrative learning better teaching and learning, the headmaster is always monitoring the performance of good teachers who are certified or not, school supervisors constantly monitors the certification of teachers especially those who have to do with teacher performance assessment. The existence of teacher competency test conducted by the Central Government in the Ministry of Education and Culture together online and throughout Indonesia with the aim of improving the competence of the teachers there are certified educators . Keywords:   Process, Certification, Teacher, Competency